Efficacy of the Novel Degludec/Aspart Insulin Co-formulation in Children and Adolescents with Type 1 Diabetes: A Real-life Experience with 1-year IDeg/Asp Therapy in Poorly Controlled and Non-compliant Patients - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (My University, 2021)
Objective: To evaluate efficacy of Degludec/Aspart (IDegAsp) insulin co-formulation in children and adolescents with poorly controlled type 1 diabetes (T1DM). Methods: A total of 50 patients with poorly-controlled T1DM on basal-bolus insulin regime and having compliance problems related to insulin injections and switched to IDegAsp were included. Data on HbA1c levels, hypoglycemic episodes, diabetic ketoacidosis (DKA) frequency and insulin doses were recorded at baseline and 1-year after the IDegAsp treatment. Results: Fifty patients (22 girls) were started on IDegAsp. The mean age and duration of diabetes were 12.9±3.4 (4-18) and 5.2±3.1 years (1.0-13.7), respectively. At the end of one year, 38 patients were still on IDegAsp, whereas 12 patients returned to their original treatments on their will. In those, who continued on IDegAsp, HbA1c levels did not change, but the number of self-reported mild-moderate hypoglycemia decreased significantly (p<0.05). In the year before switching to IDegAsp 11 DKA attacks in 9 patients were observed, whereas this decreased to 4 DKA attacks in 4 patients after 1-year of IDegAsp therapy (p=0.06). Conclusion: IDegAsp regimen could be useful in T1DM patients poorly controlled on basal-bolus insulin regimen with frequent hypoglycemia and DKA attacks as well as a poor compliance with multiple injections. Although, simplified basal-bolus regimen with IDegAsp is an attractive option for the patients with T1DM, some of the patients may not adapt to the treatment due to fixed IAsp dose of IDegAsp.
Keywords: hypoglycemia; co-formulation; diabetic ketoacidosis; IDegAsp; insulin aspart; insulin degludec; Type 1 diabetes mellitus